CRISPR/Cas9-based mono-sex breeding strategy developed in Oryzias latipes for applications in fish - Jinzhi Zhao; Lei Chen; Yi Rong; Yanlong Song; Binbin Tao; Ji Chen; Wei Hu (Aquaculture, 2026)

Benzoic acid inhibits peach root growth and lateral root emergence by disrupting auxin homeostasis through salicylic acid accumulation - Qing Rong Zhang; Jilin Yao; Feiyang Ji; Zhilin Sun; Bing Bai; Jun Zhao; Huchen Li; Yueping Liu; Qingqin Cao; Qing Zhang; Ting Ting Xiao (Plant Cell Reports, 2026)

Nitrogen uptake dynamics in coastal waters of eastern Hainan, China - Nannan Gao; Renming Jia; Zuhao Zhu; Penglan Shi; Zhao Rong; Lili Han; Silin Ni; Shan Sun; Jianzhong Su; Shuh-Ji Kao; Min Xu (Acta Oceanologica Sinica, 2026)

Inflammatory Signatures of Tinnitus in Patients and Mice - Shuai Cheng; Qi Zhao; Guiyuan Rong; Shichu Sun; Hongjie Wang; Zhiyong Tan; Yonghua Ji; You Zhou (Neuroscience Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Current warming exceeds medieval warm period in impact on Tibetan Plateau lake ecosystems - Jianan Zheng; Rong Wang; Yu Zhao; Kexin Zhu; Yanjie Zhao; Yuan Li; Ke Zhang; Hao Long; Ji Shen (Quaternary Science Reviews, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Integrating machine learning and prioritization to decipher the partitioning and risk of tire-derived chemicals in highly populated coastal regions - Nian-Nian Wu; Yuan Liu; Shan Liu; Ji-Xun Chen; Qin-Ge Zhou; Xiang-Rong Xu; Qing-Song Yang; Juan Ling; Jian-Liang Zhao (Water Research, 2026)

Non-extractable residues as the dominant fate of bisphenol A (BPA) in oxic paddy soil: formation and characterization - Yanan Zhao; Yongfeng Wang; Xiaoran Guo; Siqi Cao; Bingqi Jiang; Yao Yao; Xiaolong Liang; Rong Ji (Science of The Total Environment, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Early Temporal Dynamics of Gonadal Development and Sexually Dimorphic Gene Expression During Sex Differentiation in Mandarin Fish (Siniperca chuatsi) - Yi Rong; Yuanyuan Wang; Jinzhi Zhao; Lei Chen; Kuangxin Chen; Binbin Tao; Yanlong Song; Jianxiong Yin; Kewei Zeng; Wen Song; Wei Hu; Ji Chen (Marine Biotechnology, 2025)

Construction and validation of a predictive model for the risk of multidrug-resistant Klebsiella pneumoniae infection based on machine learning algorithms - a multicenter retrospective study - Tao Sun; Pei-Pei Wang; Jun-Ji Liu; Zhen An; Jun-Rong Zhao; Jun Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Recent advances in fluorescent aptamer-based sensors for food safety analysis - Ranran Hou; Liuqin He; Xin Ji; Xiaoxiao Rong; Yulong Yin; Xing Li; Yunxuan Weng; Xiaoying Zhao (Trends in Food Science & Technology, 2025)

Impacts of river inputs and aquaculture on nutrient dynamics in Qinglan Bay and adjacent coastal waters in East Hainan, China - Sang Wu; Zuoli Tan; Youfei Fu; Nannan Gao; Silin Ni; Rong Zhao; Penglan Shi; Lili Han; Jianzhong Su; Zhenzhen Zheng; Ehui Tan; Shuh-ji Kao; et al. (Marine Pollution Bulletin, 2025)

A millennial record of lake ecosystem responses to climatic variability in the Yellow River Source Area - Jianan Zheng; Rong Wang; Hanxiao Zhang; Shouliang Huo; Jingjing Li; Yanjie Zhao; Ji Shen (Quaternary Science Reviews, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Efficient uranium(VI) recovery from fluorinated wastewater via deferiprone ligand complexation - Juanlong Li; Yezi Hu; Zewen Shen; Huihui Jin; Rong He; Wenkun Zhu; Guixia Zhao; Zhuoyu Ji; Bin Ma; Xiangke Wang (Water Research, 2025)

Nitrogen utilization dynamics in a tropical estuary: Interplay of temperature and phytoplankton communities - Penglan Shi; Zuoli Tan; Youfei Fu; Min Nina Xu; Rong Zhao; Lihua Shang; Jin-Ming Tang; Lili Han; Shan Sun; Ehui Tan; Zhenzhen Zheng; Shuh-Ji Kao (Marine Environmental Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Polymeric PDI-based photocatalytic nanoarchitectures promoting the performance of thin film composite membrane for forward osmosis water purification - Pin Zhao; Yang Hu; Xiaoqiang An; Rong Ji; Hao Liu; Hui Zhao; Weilong Song; Yuming Dong; Xinhua Wang (Chemical Engineering Journal, 2023)

Effect of iron-loaded sludge biochar amendments on phytoremediation potential of Cr-contaminated soils by Leersia hexandra swartz - Jin-Chao Wang; Ji-Rong Zhao; Qing-Xia Huang; Li-Jiao Yang; Guo Yu; Yu-Feng Xu; Li-Heng Liu (Chemosphere, 2023)

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Photocatalysis-self-Fenton system over edge covalently modified g-C3N4 with high mineralization of persistent organic pollutants - Tongbin Lu; Hui Zhao; Liang Jian; Rong Ji; Chengsi Pan; Guangli Wang; Yuming Dong; Yongfa Zhu (Environmental Research, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Emerging Role of PD-1 in the Central Nervous System and Brain Diseases - Junli Zhao; Alexus Roberts; Zilong Wang; Justin Savage; Ru-Rong Ji (Neuroscience Bulletin, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Network parameters quantify loss of assemblage structure in human‐impacted lake ecosystems - Rong Wang; John A. Dearing; C. Patrick Doncaster; Xiangdong Yang; Enlou Zhang; Peter G. Langdon; Hui Yang; Xuhui Dong; Zhujun Hu; Min Xu; Yanjie Zhao; Ji Shen (Global Change Biology, 2019)
Lake biodiversity is an incomplete indicator of exogenous forcing insofar as it ignores underlying deformations of community structure. Here, we seek a proxy for deformation in a network of diatom assemblages comprising 452 species in 273 lakes across China. We test predictions from network theory that nodes of similar type will tend to self‐organize in an unstressed system to a positively skewed frequency distribution of nodal degree. The empirical data reveal shifts in the frequency distributions of species associations across regions, from positive skew in lakes in west China with a history of low human impacts, to predominantly negative skew amongst lakes in highly disturbed regions in east China. Skew values relate strongly to nutrient loading from agricultural activity and urbanization, as measured by total phosphorus in lake water. Reconstructions through time show that positive skew reduces with temporal intensification of human impacts in the lake and surrounding catchments, and rises as lakes recover from disturbance. Our study illustrates how network parameters can track the loss of aquatic assemblage structure in lakes associated with human pressures.

Agrobacterium tumefaciens-mediated transformation system for the important medicinal plant Dendrobium catenatum Lindl - Ji Chen; Li Wang; Jianbin Chen; Jin Huang; Fan Liu; Rong Guo; Li Yang; Aby Grabon; Ke Zhao; Fanlei Kong; Chen Liu; Mengliang Tian (In Vitro Cellular & Developmental Biology - Plant, 2018)

Genetic diversity and population structure of the northern snakehead (Channa argus Channidae: Teleostei) in central China: implications for conservation and management - Ruo-Jin Yan; Gui-Rong Zhang; Xiang-Zhao Guo; Wei Ji; Kun-Ci Chen; Gui-Wei Zou; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics, 2018)

p70S6K activation promotes the transdifferentiation of fibroblasts to myofibroblasts in pterygium tissue growth on the cornea - Xin-Rong Zhao; Ming-Chang Zhang; Hua-Tao Xie; Nan Ji; Le-Tian Sun (Biotechnology Letters, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

Are habitat fragmentation, local adaptation and isolation‐by‐distance driving population divergence in wild rice O ryza rufipogon ? - Yao Zhao; Klaas Vrieling; Hui Liao; Manqiu Xiao; Yongqing Zhu; Jun Rong; Wenju Zhang; Yuguo Wang; Ji Yang; Jiakuan Chen; Zhiping Song (Molecular Ecology, 2013)
Habitat fragmentation weakens the connection between populations and is accompanied with isolation by distance ( IBD ) and local adaptation (isolation by adaptation, IBA ), both leading to genetic divergence between populations. To understand the evolutionary potential of a population and to formulate proper conservation strategies, information on the roles of IBD and IBA in driving population divergence is critical. The putative ancestor of A sian cultivated rice ( O ryza sativa ) is endangered in C hina due to habitat loss and fragmentation. We investigated the genetic variation in 11 C hinese O ryza rufipogon populations using 79 microsatellite loci to infer the effects of habitat fragmentation, IBD and IBA on genetic structure. Historical and current gene flows were found to be rare ( m h = 0.0002–0.0013, m c = 0.007–0.029), indicating IBD and resulting in a high level of population divergence ( F ST = 0.343). High within‐population genetic variation ( H E = 0.377–0.515), relatively large effective population sizes ( N e = 96–158), absence of bottlenecks and limited gene flow were found, demonstrating little impact of recent habitat fragmentation on these populations. Eleven gene‐linked microsatellite loci were identified as outliers, indicating local adaptation. Hierarchical AMOVA and partial M antel tests indicated that population divergence of C hinese O . rufipogon was significantly correlated with environmental factors, especially habitat temperature. Common garden trials detected a significant adaptive population divergence associated with latitude. Collectively, these findings imply that IBD due to historical rather than recent fragmentation, followed by local adaptation, has driven population divergence in O . rufipogon .

Induction of annexin by heavy metals and jasmonic acid in Zea mays - Mei-Liang Zhou; Xiong-Bang Yang; Qian Zhang; Ming Zhou; En-Ze Zhao; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Molecular and pathogenic characterization of new Xanthomonas oryzae pv. oryzae strains from the coastline region of Fangchenggang city in China - Shu-Qing Yang; Shu-Yan Liu; Shuai Zhao; Yan-Hua Yu; Rong-Bai Li; Cheng-Jie Duan; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

Microspore embryogenesis and production of haploid and doubled haploid plants in carrot (Daucus carota L.) - Jin-Rong Li; Fei-Yun Zhuang; Cheng-Gang Ou; Hong Hu; Zhi-Wei Zhao; Ji-Hua Mao (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Cloning, Characterization and Functional Analysis of a Phenylalanine Ammonia-lyase Gene (FtPAL) from Fagopyrum tataricum Gaertn - Cheng Lei Li; Yue Chen Bai; Hui Chen; Hai Xia Zhao; Ji Rong Shao; Qi Wu (Plant Molecular Biology Reporter, 2012)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Molecular Cloning and Characterization of a Novel Human C4orf13 Gene, Tentatively a Member of the Sodium Bile Acid Cotransporter Family - Xianqiong Zou; Dianzuo Wang; Guanzhou Qiu; Chaoneng Ji; Feng Jin; Maoqing Wu; Huarui Zheng; Xin Li; Liyun Sun; Yu Wang; Rong Tang; Robert Chunhua Zhao; et al. (Biochemical Genetics, 2005)

Characterization of a human Sec14-like protein cDNA SEC14L3 highly homologous to human SPF/TAP - Xin Ye; Chaoneng Ji; Gang Yin; Rong Tang; Li Zeng; Shaohua Gu; Kang Ying; Yi Xie; Robert Chunhua Zhao; Yumin Mao (Molecular Biology Reports, 2004)

Application of geographical parameter database to establishment of unit population database - Chun Dong; Rong Zhao; Ji-ping Liu; Gui-xin Wang; Xi-zhi Wu (Chinese Geographical Science, 2003)